Disruption of the Higher Education System Has Impact on the High Rate of Educated Unemployment in Indonesia - Syafril, Syafril; Sofia; Jannah, Tannia; Rifai, Muhamaad (Jurnal Ekonomi Dan Statistik Indonesia, 2025)
This research aims to describe the impact of Disruption of the Higher Education System Has Impact on the High Rate of Educated Unemployment In Indonesia. This research uses a descriptive exploratory approach with a literature review and direct observation of the research subjects. The descriptive approach is used to explain problems or phenomena related to the disruption of higher education industrialization, while the exploratory approach is used to conceptually explain the disruption of higher education industrialization. The literature review method is conducted by searching for research data or information through reading scientific journals, reference books, and published materials available in libraries and the internet. This study also uses direct participant observation techniques, which the researcher conducted while gathering information as a lecturer. The results of this study indicate that the disruption of the higher education system has had an impact on the high level of educated unemployment in Indonesia. From this research, it is hoped that the government and higher education institutions can improve the quality of higher education institutions and the human resources (HR) of their graduates so they can compete globally.